(untitled) (Quinto Sol, 2013)
The objective of this work is to analyze the changes that occurred within the tribes of “indios amigos” located on the Buenos Aires frontier, as a consequence of the close relationship with white society. In this regard, the following issues will be examined: a) the influence of the ration system allocated to the tribes; b) the function that internal processes of change fulfilled in relation to the power of the chief; c) the existence of the border, which frames the transformations operated in these indigenous groups.